2019
DOI: 10.1200/jco.19.00177
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Relapsed and Refractory Solid Tumors With Ex Vivo Expanded Multi-Tumor Associated Antigen Specific Cytotoxic T Lymphocytes: A Phase I Study

Abstract: PURPOSE Tumor-associated antigen cytotoxic T cells (TAA-Ts) represent a new, potentially effective and nontoxic therapeutic approach for patients with relapsed or refractory solid tumors. In this first-in-human trial, we investigated the safety of administering TAA-Ts that target Wilms tumor gene 1, preferentially expressed antigen of melanoma, and survivin to patients with relapsed/refractory solid tumors. MATERIALS AND METHODS TAA-T products were generated from autologous peripheral blood and infused over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 46 publications
0
59
0
Order By: Relevance
“…Novel T-cell platforms targeting multiple antigens highlight the potential to overcome antigen loss in pediatric solid tumors. The firstin-human trial evaluating tumor-specific T cells targeting Wilms tumor gene 1 and survivin showed safe administration and a 73% response rate in 15 pediatric patients with relapsed/refractory solid tumors (13). Gamma-delta (gd) T cells constitute another viable cell product given their T cell-like properties, lack of MHC restriction, presence of CD16, and ability to mediate antibody-dependent cellular cytotoxicity (ADCC).…”
Section: Current Immunotherapeutic Approaches For Pediatric Solid Tumorsmentioning
confidence: 99%
“…Novel T-cell platforms targeting multiple antigens highlight the potential to overcome antigen loss in pediatric solid tumors. The firstin-human trial evaluating tumor-specific T cells targeting Wilms tumor gene 1 and survivin showed safe administration and a 73% response rate in 15 pediatric patients with relapsed/refractory solid tumors (13). Gamma-delta (gd) T cells constitute another viable cell product given their T cell-like properties, lack of MHC restriction, presence of CD16, and ability to mediate antibody-dependent cellular cytotoxicity (ADCC).…”
Section: Current Immunotherapeutic Approaches For Pediatric Solid Tumorsmentioning
confidence: 99%
“…An alternative immunotherapeutic strategy would be to transfer allogeneic MCPyV-specific T cells derived from an HLA matched healthy donor using peptide libraries of the viral oncoproteins. ACT with peptide library-pulsed ex vivo expanded virus or tumor antigen-specific T cells has been used with success in multiple clinical trials to treat viral infections, EBV-driven lymphomas, and solid tumors (15)(16)(17). MCPyV TAg specific CD4 + , but not CD8 + , T cells have been found in healthy donors and have not been evaluated for ACT (12,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Bollard is hopeful that T cell–based therapies will find clinical applications in solid tumors, which have not been as amenable as hematological tumors. In a phase I study in heavily pretreated patients with solid tumors, autologous multiantigen‐specific T cell treatment was safe, with some patients experiencing prolonged disease stabilization 39 …”
Section: Strategies To Overcome Tumor Immune Evasionmentioning
confidence: 99%